FinTech in the post-pandemic future / Wan Nailah Abdullah - Abdullah, Wan Nailah (Faculty of Accountancy, 2021)
COVID-19 pandemic has created economic crises worldwide. Despite generous aid programs provided by governments all over the world for their people, uncertainty prevails as the future economy remains a mystery. FinTech, an acronym for “financial technology”, that is used to augment, streamline, digitize or disrupt traditional financial services (Walden, 2020), is a sector that was performing great before the pandemic. FinTech is at the crossroads between surviving the crisis and abundance of opportunities in facing the future.